Weaknesses in mental health care: perceptions of primary health care professionals in times of COVID-19 (Research, Society and Development, 2021)
Aim: to analyze the perception of health professionals in Primary Health Care about the weaknesses related to mental health care in their daily work, and identify proposals to qualify assistance to this demand, amidst the pandemic caused by COVID-19. Method: it is an action-research, developed in a municipality in the north of Rio Grande do Sul, Brazil, whose participants were 8 professionals from a Basic Health Unit. The information was produced in December 2020, through a conversation circle. Data treatment was guided through content analysis. Results: the weaknesses in care involved the centralization of treatment based on psychotropic drugs, inadequate care for children and adolescents in social vulnerability, as well as users in mental suffering and their families during the COVID-19 pandemic period. Continuing education, the development of mental health actions to the population and comprehensive care emerged as proposals to qualify care. Conclusion: it was identified that a restructuring of mental health care in Primary Health Care is necessary since the prescription of psychotropic drugs is the first and only treatment option for users. It is understood that nurses, on having adequate competencies (knowledge, habilities and attitudes), can contribute to the qualification of mental health care in Primary Health Care.